The Danzig Gun: A Rare Decorated Bronze Handgun of the 15th Century. (3rd July 2015) - Ferguson, Jonathan
Abstract : For the first time in English, this short article describes an important and early handgun of approximately 1400AD, originally found near Danzig in the 1920s and recently acquired by the Royal Armouries Museum. The gun is at once of characteristic design, yet exhibits particular decorative features that set it apart from other known examples referenced herein. The note goes on to explore the possible significance of the decoration, specifically the bearded faces cast around the muzzle. It note closes by identifying and differentiating known modern copies of this piece.